The Effects of Social Interaction and Communication on the Improvement of Communication Proficiency in Bangladesh - Shamerul Huda, Khondaker Mohammod; Shaherul Huda, Khondaker Mohammod; Shariful Huda, Khondaker Mohammod; Sk. Moniruzzaman (The Jahangirnagar Review, 2024)
Recent times have increasingly shown the importance of communication skills, be it for students or for working adults. There is almost no job sector that does not require ample communication skills. However, despite having much focus in other countries in Bangladesh, there is not much importance put on the development of communication yet. There are many factors that can contribute to development, but the most modern and indirect method is occurring through social interaction, both physically and via social media. They lead to interaction and communication among many individuals, leading to shared ideas and innovation. The outcome and significance of the relationship between these two variables have not been investigated. There have been some studies of social interaction and cognitive development (Hinde, 1985), but these are in the past, and it is important to know the effect right now in a developing country such as Bangladesh. It is expected to see a high correlation between social interaction and communication skills after the data analysis.